Industrial Fermentation of Auxenochlorella protothecoides for Production of Biodiesel and Its Application in Vehicle Diesel Engines - Xiao, Yibo; Lu, Yue; Dai, Junbiao; Wu, Qingyu (Frontiers in Bioengineering and Biotechnology, 2015)
Microalgae-derived biodiesel has been regarded as a promising alternative for fossil diesel. However, the commercial production of microalgal biodiesel was halted due to its high cost. Here, we presented a pilot study on the industrial production of algal biodiesel. We began with the heterotrophic cultivation of Auxenochlorella protothecoides in a 60 m3 fermentor that produced biomass at 3.81 g L-1 day-1 with a neutral lipid content at 51%. Next, we developed plate-frame filter, natural drying and ball milling methods to harvest, dry and extract oil from the cells at low cost. Additionally, algal biodiesel was produced for a vehicle engine test, which indicated that the microalgal biodiesel was comparable to fossil diesel but resulted in fewer emissions of particulate matter, carbon monoxide and hydrocarbon. Altogether, our data suggested that the heterotrophic fermentation of A. protothecoides could have the potential for the future industrial production of biodiesel.